Clinical, pathologic, and molecular features of inflammatory myofibroblastic tumors in children and adolescents. Issue 5 (2nd December 2021) - Pire, Aurore; Orbach, Daniel; Galmiche, Louise; Berrebi, Dominique; Irtan, Sabine; Boudjemaa, Sabah; Brisse, Hervé J.; Berteloot, Laureline; Moalla, Salma; Mussini, Charlotte; Philippe‐Chomette, Pascale; Tilea, Bogdana; et al.
Abstract: Background: Inflammatory myofibroblastic tumors (IMT) are rare, intermediate malignant tumors harboring frequent somatic molecular rearrangements. The management of IMT has not been standardized. Methods: A retrospective multicenter study was conducted on all pediatric patients treated for IMT between 2000 and 2019. Results: This series included 39 cases of IMT, with a median age at diagnosis of 7 years (range 20 days to 16 years). Tumor location included pelvis‐abdomen ( n = 16), thorax ( n = 14), head and neck ( n = 7), and limbs ( n = 2). One patient had metastatic disease. Immunochemistry showed 21/39 (54%) anaplastic lymphoma kinase (ALK)‐positive tumors. Somatic tyrosine kinase rearrangement was present in 31/36 (86%) of the tumors analyzed: 21 ALK, five ROS1, and five NTRK. Immediate surgery was performed in 24 patients (62%), with adjuvant therapy for three patients. Delayed surgery after neoadjuvant therapy was possible in 10 cases. Exclusive systemic therapy was delivered to four patients; one patient with orbital IMT was managed by watchful waiting. After a median follow‐up of 33 months (range 5–124), eight (20%) recurrences/progressions occurred after surgery (seven after primary surgery and one after delayed surgery), after a median interval of 7 months (range 2–21), all in thoracic locations. The 3‐year overall and disease‐free survivals were 96.8% (95% CI: 79.2%–94.0%) and 77.4% (95% CI: 59.6%–88.1%), respectively. Relapses/progressions were more common in patients with a thoracic primary ( p < .001) or after incomplete surgery with no adjuvant therapy ( p = .027). Conclusion: Surgery is effective in most cases of pediatric IMT. Systematic analysis of tyrosine kinase rearrangement is recommended. When the tumor is deemed only partially resectable to preserve organs and function, neoadjuvant therapy may be proposed to allow adequate conservative surgery.